FIELD SURVEYS OF OZONE SYMPTOMS IN EUROPE. PROBLEMS, RELIABILITY AND SIGNIFICANCE FOR ECOSYSTEMS - Bussotti, F.; Pollastrini, M. (Annali di Botanica, 2015)
The ICP-Forest program for the monitoring of forest conditions includes the assessment of ozone symptoms in the European forests. This contribute to discussion points out the problems related to the recognition of such symptoms, with a special focus on the difficulties to extend the results obtained in experimental conditions to woody plant species growing in the field. Non specific symptoms (such as reddening, yellowing, early senescence and leaf loss), and the concurrent action of modifying factors (high light, drought, nutrient deficiency, pest attack and fungi) make the recognition elusive. In these cases, the action of ozone cannot be proven or excluded with “ad hoc” experiments. Apparently “good” bioindicators (Rubus sp. Cornus sp. pl., Prunus sp. pl., Viburnum sp. pl. etc.) are not suitable to assess the impact of ozone on vegetation. Symptoms are not necessarily related to the ozone dose taken up by stomata, and don’t are reliable indicator for biomass and productivity losses. Symptoms can be considered an epiphenomenon of more complex ecosystem processes.